UJI PESTISIDA NABATI TERHADAP HAMA DAN PENYAKIT TANAMAN - MOKHAMAD IRFAN (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
The Loss of crop productivity can reach 30-35% if not use pesticide. The other hand, to use of pesticides can be caused environmental problems and human healthy. This research aims to develop biopesticides for pests and plant diseases. It was conducted at the PEM laboratory UIN Suska Riau and on land, from July to November 2015. The sourches were extracts from Andropogon nardus, Annona muricata leaves, Ageratum conyzoides, Piper aduncun fructus, Nicotiana tabacum leaves, Tinospora crispa, Azadirachta indica leaves, Allium sativum and Piper betle leaves. Each the source was macerated in alcohol 50% for 24 hours and then distilled at a temperature of 60 °C until all the alcohol evaporates. The experimental Design was complete random design with 7 treatments (control, 20%, 40%, 60%, 80%, 100% and chemical pesticides as positif control) and 3 replicates. Parameters of the test biopesticides to disease performed in vitro with measure the resistance zones and for mealybugs and Gryllus assimilis in vivo with the pest mortality. Biopesticide test in vitro for the bacteria that causes carrot root rot has not been able to kill microbes. The mortality rate mealybugs begins before 1 hour observation at the treatment biopesticide concentration of 80%, 100% and control positif. Provision of different concentrations of biopesticides, does not the increased mortality of Gryllus assimilis. This shows that the power to kill biopesticide still well below chemical pesticides, but the pest is still alive no appetite as antifeedant effect of the biopesticide. So biopesticide application does not have to kill the target pest. Need follow-up and development of this research and other pests.